Compressibility and Moelwyn-Hughes Parameter of NaI crystals under high pressure, as the function of thermal properties - Khan, Arun Kumar (BIBECHANA, 2012)
The credit for the commencement of inter ionic potential function goes to Born and Lande, one of whose milestone has been their expression into inverse function. Similarly, Born and Mayer also proposed the exponential function of the potential for the repulsive component. However none of them could get the desired success. Subsequently, many more prominent scientists devoted their effort towards these thermal properties of the crystals, among which the endeavour of Jha and Thakur cannot be overlooked, who proposed a new interionic function to observe the properties of ionic crystal under high pressure. During its formulation they included both an inverse power function due to Born and Lande and an exponential function due to to Born and Mayer. Appreciably, Jha and Khan used it for studying the hyped thermal properties of NAI and CsI crystal under high pressure up to 100 Kilo bar. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7180 BIBECHANA 9 (2013) 88-91